Economic growth, development, and planning - Ghosh, B. N.; Ghosh, Rama. (New Delhi : Deep & Deep Publications, 1991)
The book covers the following chapters: Underdevelopment and Growth Process, Some Theories of Development; Physical Capital and Domestic Resources; Agricultural Sector; Population Problem and Utilisation of Human Resources; Organisational and Industrial Development; Monetary Fiscal Policies; Foreign Sector; Growth Models; Fundamentals of Development Planning; Types of Planning; Planning Methodology and Process (Stages); Planning Techniques and Tools; Economic Planning: Problems and Prospects; Planning Abroad; Indian Planning; Indian Development: Some current Issues.
With reference to India.
Includes index.
Includes bibliographical references (p. [719]-724).
rpm 16/11/2017
Loans
Keywords: Economic development; Economic policy; Economic growth; Development and planning- economic; India